PERAN BANK SYARIAH DI DALAM PEMBANGUNAN EKONOMI: Analisis Teoritis Atas Mobilisasi, Alokasi dan Utilisasi Sumber Daya Ekonomi - Ahmad Mansur (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2011)
In our modern time, people will not be able to live without having involved with the financial institution. Nowadays, most of the economic and business transaction is done through the financial institution especially banking system. It is no doubt that the financial institutions have played very significant role in supporting economic development. Since we are interested in interest-free banking system, we will investigate the role of Islamic banking in economic development in Indonesia. This research is literature and library research, in the sense that it reviews the role of Islamic banking in economic development conceptually and theoretically, it analyzes the role of bank in mobilization, allocation and utilization of its resources and make a comparative analysis between what have been done by Islamic bank vis a vis conventional bank in terms of their performance in mobilization, allocation and utilization of their resources in helping economic development. This research concludes that Islamic bank, despite it operates without interest and does its operation with the principle of profit and loss system; it performs well in doing mobilization, allocation and utilization of its resources for economic development. It performs well in saving mobilization, income and wealth generation and asset accumulation as well as credit financing within syariah framework by implementing principles such as Murabaha andMudarabah financing. This research also found that the Islamic bank average growth rate of asset, saving mobilization and credit financing during ten years of this study is better than that of conventional bank, though its return on asset (ROA) is still lower than that of the conventional bank. In line with this conclusion, what is urgent to be taken in further study is how far the Islamic banks channel their resources into riskier projects, such as Mudarabah financing projects, since the higher the risk, the higher the profit. It is also urgent to take further quantitative research on how far the presence of the Islamic banks has a positive impact on economic development.